Childhood maltreatment and eating disorders: a prospective investigation - Talmon, Anat (Child maltreatment, 2022)
Objectives:To determine whether childhood maltreatment is a risk factor for two eating disorders (anorexia nervosa and bulimia nervosa) using objective and subjective case definitions.Methods:Using a prospective cohorts design, children with documented cases of physical abuse, sexual abuse, and neglect (ages 0-11) from 1967 to 1971 in a Midwestern metropolitan county area were matched on age, race, sex, and approximate family socioeconomic status with non-maltreated children. Both groups were followed up. Retrospective self-reports about childhood maltreatment were collected at age 29. DSM-IV anorexia nervosa (AN) and bulimia nervosa (BN) disorders were assessed at age 41 (N = 807). Logistic and linear regression results are reported.Results:Using documented cases, childhood maltreatment was not a significant risk factor for AN or BN diagnoses or symptoms in adulthood. However, adults who retrospectively reported any maltreatment and physical and sexual abuse reported significantly more symptoms of AN than those who did not.Conclusions:The prediction that childhood maltreatment is a risk factor for anorexia nervosa and bulimia nervosa was partially supported in this longitudinal study. While misattribution of cases might have occurred, these results suggest that researchers and clinicians should use caution in drawing inferences about these relationships and designing interventions.